Exotic massive 3D gravity - Mehmet Ozkan; Yi Pang; Paul K. Townsend (Journal of High Energy Physics, 2018)
Abstract The linearized equations of “New Massive Gravity” propagate a parity doublet of massive spin-2 modes in 3D Minkowski spacetime, but a different non-linear extension is made possible by “third-way” consistency. There is a “Chern-Simons-like” action, as for other 3D massive gravity models, but the new theory is “exotic”: its action is parity odd. This “Exotic Massive Gravity” is the next-to-simplest case in an infinite sequence of third-way consistent 3D gravity theories, the simplest being the “Minimal Massive Gravity” alternative to “Topologically Massive Gravity”.